Framing English as a Medium of Instruction Within the Iberian-American Spanish-Speaking Education Contexts - Wilder Yesid Escobar-Alméciga (Universidad Nacional de Colombia, 2022)
Education in Spain and Latin America has been experiencing an ever-increasing use of English as a medium of instruction at all levels and across curricula. Bringing the vast research-literature into a reflective dialogue is paramount to advancing the discipline and to refining English teaching practices. As such, this literature review systematically situates English-as-a-medium-of-instruction literature related to higher education within the Iberian-American school contexts where Spanish was the students' first language. Thus, the paper asserts that while research that addresses methodological approaches, processes, procedures, and their effects in instruction is significant, there is still a pressing need for framing English-as-a-medium-of-instruction research within the reciprocal relationship existing among communication, classroom culture, social values, the classroom climate for learning, and ultimately, the students' learning.